Teaching and learning guide for audiovisual speech perception: A new approach and implications for clinical populations. - Irwin, Julia; Turcios, Jacqueline (Language and linguistics compass, 2017)
0 citations (Crossref) [2023-10-31] Place: England Irwin, Julia. Haskins Laboratories, New Haven, CT, USA. Irwin, Julia. Southern Connecticut State University, New Haven, CT, USA. Turcios, Jacqueline. Haskins Laboratories, New Haven, CT, USA. Turcios, Jacqueline. Southern Connecticut State University, New Haven, CT, USA.
Keywords: dept.psy

A familiarization protocol facilitates the participation of children with asd in electrophysiological research - Turcios, Jacqueline; Cook, Barbara; Irwin, Julia; Rispoli, Taylor; Landi, Nicole (JoVE (Journal of Visualized Experiments), 2017)
This paper includes a detailed description of a familiarization protocol, which is used as an integral component of a larger research protocol to collect electroencephalography (EEG) data and Event-Related Potentials (ERPs). At present, the systems available for the collection of high-quality EEG/ERP data make significant demands on children with developmental disabilities, such as those with an Autism Spectrum Disorder (ASD). Children with ASD may have difficulty adapting to novel situations, tolerating uncomfortable sensory stimuli, and sitting quietly. This familiarization protocol uses Evidence-Based Practices (EBPs) to increase research participants' knowledge and understanding of the specific activities and steps of the research protocol. The tools in this familiarization protocol are a social narrative, a visual schedule, the Premack principle, role-playing, and modeling. The goal of this familiarization protocol is to increase understanding and agency and to potentially reduce anxiety for child participants, resulting in a greater likelihood of the successful completion of the research protocol for the collection of EEG/ERP data.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-947-783-936-351, pop00167 tex.type: [object Object]
Keywords: dept.cmd; dept.psy

Development of an audiovisual speech perception app for children with autism spectrum disorders - Irwin, Julia; Preston, Jonathan; Brancazio, Lawrence; D'Angelo, Michael; Turcios, Jacqueline (Clinical Linguistics & Phonetics, 2015)
Perception of spoken language requires attention to acoustic as well as visible phonetic information. This article reviews the known differences in audiovisual speech perception in children with autism spectrum disorders (ASD) and specifies the need for interventions that address this construct. Elements of an audiovisual training program are described. This researcher-developed program delivered via an iPad app presents natural speech in the context of increasing noise, but supported with a speaking face. Children are cued to attend to visible articulatory information to assist in perception of the spoken words. Data from four children with ASD ages 8-10 are presented showing that the children improved their performance on an untrained auditory speech-in-noise task.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-073-168-350-692 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Attention; Audiovisual Aids; Audiovisual app; Autism spectrum disorder; Child; Child Development Disorders; Pervasive; Comprehension; Humans; Lipreading; Male; Mobile Applications; Pattern Recognition; Visual; Phonetics; Semantics; Speech Perception; Speech perception; attention; audiovisual aid; child; comprehension; dept.cmd; dept.hls; dept.psy; human; lip reading; male; mobile application; pattern recognition; phonetics; psychology; semantics; speech perception

Electrophysiological Indices of Audiovisual Speech Perception in the Broader Autism Phenotype. - Irwin, Julia; Avery, Trey; Turcios, Jacqueline; Brancazio, Lawrence; Cook, Barbara; Landi, Nicole (Brain sciences, 2017)
When a speaker talks, the consequences of this can both be heard (audio) and seen (visual). A novel visual phonemic restoration task was used to assess behavioral discrimination and neural signatures (event-related potentials, or ERP) of audiovisual processing in typically developing children with a range of social and communicative skills assessed using the social responsiveness scale, a measure of traits associated with autism. An auditory oddball design presented two types of stimuli to the listener, a clear exemplar of an auditory consonant-vowel syllable /ba/ (the more frequently occurring standard stimulus), and a syllable in which the auditory cues for the consonant were substantially weakened, creating a stimulus which is more like /a/ (the infrequently presented deviant stimulus). All speech tokens were paired with a face producing /ba/ or a face with a pixelated mouth containing motion but no visual speech. In this paradigm, the visual /ba/ should cause the auditory /a/ to be perceived as /ba/, creating an attenuated oddball response; in contrast, a pixelated video (without articulatory information) should not have this effect. Behaviorally, participants showed visual phonemic restoration (reduced accuracy in detecting deviant /a/) in the presence of a speaking face. In addition, ERPs were observed in both an early time window (N100) and a later time window (P300) that were sensitive to speech context (/ba/ or /a/) and modulated by face context (speaking face with visible articulation or with pixelated mouth). Specifically, the oddball responses for the N100 and P300 were attenuated in the presence of a face producing /ba/ relative to a pixelated face, representing a possible neural correlate of the phonemic restoration effect. Notably, those individuals with more traits associated with autism (yet still in the non-clinical range) had smaller P300 responses overall, regardless of face context, suggesting generally reduced phonemic discrimination.
8 citations (Crossref) [2023-10-31] Place: Switzerland Irwin, Julia. Haskins Laboratories, New Haven, CT 06511, USA. julia.irwin@yale.edu. Irwin, Julia. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, USA. julia.irwin@yale.edu. Avery, Trey. Haskins Laboratories, New Haven, CT 06511, USA. trey.avery@yale.edu. Turcios, Jacqueline. Haskins Laboratories, New Haven, CT 06511, USA. jacqueline.turcios@yale.edu. Turcios, Jacqueline. Department of Communication Disorders, Southern Connecticut State University, New Haven, CT 06515, USA. jacqueline.turcios@yale.edu. Brancazio, Lawrence. Haskins Laboratories, New Haven, CT 06511, USA. brancaziol1@southernct.edu. Brancazio, Lawrence. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, USA. brancaziol1@southernct.edu. Cook, Barbara. Department of Communication Disorders, Southern Connecticut State University, New Haven, CT 06515, USA. cookb5@southernct.edu. Landi, Nicole. Haskins Laboratories, New Haven, CT 06511, USA. nicole.landi@yale.edu. Landi, Nicole. Psychological Sciences, University of Connecticut, Storrs, CT 06269, USA. nicole.landi@yale.edu.
Keywords: Article; Audiovisual speech perception; Broader autism phenotype; Development; ERP; audiovisual aid; audiovisual equipment; audiovisual speech perception; autism; behavior; broader autism phenotype; child; clinical article; dept.cmd; dept.hls; dept.psy; development; electrophysiology; female; human; male; participant observation; phenotype; social adaptation; social competence; speech perception; stimulus; vision test

Electrophysiological Indices of Audiovisual Speech Perception: Beyond the McGurk Effect and Speech in Noise. - Irwin, Julia; Avery, Trey; Brancazio, Lawrence; Turcios, Jacqueline; Ryherd, Kayleigh; Landi, Nicole (Multisensory research, 2018)
Visual information on a talker's face can influence what a listener hears. Commonly used approaches to study this include mismatched audiovisual stimuli (e.g., McGurk type stimuli) or visual speech in auditory noise. In this paper we discuss potential limitations of these approaches and introduce a novel visual phonemic restoration method. This method always presents the same visual stimulus (e.g., /ba/) dubbed with a matched auditory stimulus (/ba/) or one that has weakened consonantal information and sounds more /a/-like). When this reduced auditory stimulus (or /a/) is dubbed with the visual /ba/, a visual influence will result in effectively 'restoring' the weakened auditory cues so that the stimulus is perceived as a /ba/. An oddball design in which participants are asked to detect the /a/ among a stream of more frequently occurring /ba/s while either a speaking face or face with no visual speech was used. In addition, the same paradigm was presented for a second contrast in which participants detected /pa/ among /ba/s, a contrast which should be unaltered by the presence of visual speech. Behavioral and some ERP findings reflect the expected phonemic restoration for the /ba/ vs. /a/ contrast; specifically, we observed reduced accuracy and P300 response in the presence of visual speech. Further, we report an unexpected finding of reduced accuracy and P300 response for both speech contrasts in the presence of visual speech, suggesting overall modulation of the auditory signal in the presence of visual speech. Consistent with this, we observed a mismatch negativity (MMN) effect for the /ba/ vs. /pa/ contrast only that was larger in absence of visual speech. We discuss the potential utility for this paradigm for listeners who cannot respond actively, such as infants and individuals with developmental disabilities.
8 citations (Crossref) [2023-10-31] Place: Netherlands Irwin, Julia. Haskins Laboratories, New Haven, CT, USA. Irwin, Julia. Southern Connecticut State University, New Haven, CT, USA. Avery, Trey. Haskins Laboratories, New Haven, CT, USA. Brancazio, Lawrence. Haskins Laboratories, New Haven, CT, USA. Brancazio, Lawrence. Southern Connecticut State University, New Haven, CT, USA. Turcios, Jacqueline. Haskins Laboratories, New Haven, CT, USA. Turcios, Jacqueline. Southern Connecticut State University, New Haven, CT, USA. Ryherd, Kayleigh. Haskins Laboratories, New Haven, CT, USA. Ryherd, Kayleigh. University of Connecticut, Storrs, CT, USA. Landi, Nicole. Haskins Laboratories, New Haven, CT, USA. Landi, Nicole. University of Connecticut, Storrs, CT, USA.
Keywords: Audio-visual speech; Audio-visual stimulus; Audiovisual; Audiovisual speech perception; Auditory stimuli; Developmental disability; ERP; Electrophysiology; Enterprise resource planning; Mismatch negativity; Phonemic restoration; Potential utility; Restoration; Speech; Speech recognition; Visual information; dept.psy; peer-reviewed; phonemic restoration

Neural and Behavioral Differences in Speech Perception for Children With Autism Spectrum Disorders Within an Audiovisual Context - Irwin, Julia; Harwood, Vanessa; Kleinman, Daniel; Baron, Alisa; Avery, Trey; Turcios, Jacqueline; Landi, Nicole (Journal of Speech, Language, and Hearing Research, 2023)
Purpose: Reduced use of visible articulatory information on a speaker's face has been implicated as a possible contributor to language deficits in autism spectrum disorders (ASD). We employ an audiovisual (AV) phonemic restoration paradigm to measure behavioral performance (button press) and event-related potentials (ERPs) of visual speech perception in children with ASD and their neurotypical peers to assess potential neural substrates that contribute to group differences. Method: Two sets of speech stimuli, /ba/–“/a/” (“/a/” was created from the /ba/ token by a reducing the initial consonant) and /ba/–/pa/, were presented within an auditory oddball paradigm to children aged 6–13 years with ASD (n = 17) and typical development (TD; n = 33) within two conditions. The AV condition contained a fully visible speaking face; the pixelated (PX) condition included a face, but the mouth and jaw were PX, removing all articulatory information. When articulatory features were present for the /ba/–“/a/” contrast, it was expected that the influence of the visual articulators would facilitate a phonemic restoration effect in which “/a/” would be perceived as /ba/. ERPs were recorded during the experiment while children were required to press a button for the deviant sound for both sets of speech contrasts within both conditions. Results: Button press data revealed that TD children were more accurate in discriminating between /ba/–“/a/” and /ba/–/pa/ contrasts in the PX condition relative to the ASD group. ERPs in response to the /ba/–/pa/ contrast within both AV and PX conditions differed between children with ASD and TD children (earlier P300 responses for children with ASD). Conclusion: Children with ASD differ in the underlying neural mechanisms responsible for speech processing compared with TD peers within an AV context.
0 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Electrophysiology of perception and processing of phonological information as indices of toddlers' language performance - Harwood, Vanessa; Preston, Jonathan; Grela, Bernard; Roy, Dooti; Harold, Olivia; Turcios, Jacqueline; Andrada, Kiyomi; Landi, Nicole (Journal of Speech Language and Hearing Research, 2017)
Purpose: The toddler years are a critical period for language development and growth. We investigated how event-related potentials (ERPs) to repeated and novel nonwords are associated with clinical assessments of language in young children. In addition, nonword repetition (NWR) was used to measure phonological working memory to determine the unique and collective contribution of ERP measures of phonemic discrimination and NWR as predictors of language ability. Method: Forty children between the ages of 24-48 months participated in an ERP experiment to determine phonemic discrimination to repeated and novel nonwords in an old/new design. Participants also completed a NWR task to explore the contribution of phonological working memory in predicting language. Results: ERP analyses revealed that faster responses to novel stimuli correlated with higher language performance on clinical assessments of language. Regression analyses revealed that an earlier component was associated with lower level phonemic sensitivity, and a later component was indexing phonological working memory skills similar to NWR. Conclusion: Our findings suggest that passive ERP responses indexing phonological discrimination and phonological working memory are strongly related to behavioral measures of language.
Citation Key Alias: lens.org/016-284-901-764-293 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Brain; Child Language; Child; Preschool; Discrimination (Psychology); Electroencephalography; Evoked Potentials; Female; Humans; Language Tests; Male; Memory; Short-Term; Pattern Recognition; Physiological; Phonetics; Reaction Time; Regression Analysis; Signal Processing; Computer-Assisted; Speech Perception; adult; brain; child; clinical article; dept.psy; electroencephalography; event related potential; evoked response; female; human; language ability; language development; language test; male; pattern recognition; perception; perceptive discrimination; phonetics; physiology; preschool child; reaction time; regression analysis; short term memory; signal processing; speech perception; stimulus; working memory; young adult; ⚠️ Invalid DOI